A religião na obra de Sigmund Freud: aspectos antropológicos e metapsicológicos - Souza Neto, Carlos Silvano de (2021)
The theme of religion in Sigmund Freud's work is a subject generally guided by the controversy of his atheism. However, this preconceived observation suppresses the more complex notion of how this theme carries great importance in his work. Religion is a theme that runs through Freud's research, from the first decades to the end of his life, as a researcher of human nature. In this sense, it is possible to understand that Freud evidence the religion as a thematic element in the analysis of culture. Furthermore, this theme allows psychoanalytic investigation to access a variety of human issues, and at the same time mobilizes a field of dialogue capable of providing the formulation of metapsychological concepts that help in understanding both individual psychic life and the dynamics of social and cultural phenomena. This understanding is relevant because, for Freud, there is no difference between cultural psychology and that oriented to observe and explain the phenomena of individual psychism in the clinic. In this way, studying a cultural theme allows the psychoanalyst, and the researcher of the human sciences in general, a valuable understanding of human nature. Thus, this dissertation contributes as a guide for those interested in the subject, Freud and religion, as it echoes and walks through the various texts that the author directly and indirectly addresses this subject. Freud follows the theme of religion through two dimensions in his theory: on the one hand, metapsychology, that is, conceptual deductions about psychic functioning are used to explain religious phenomena in their psychological foundations. On the other hand, Freud conducts his investigations through an anthropology, and thus assumes that religion functions in culture through the exercise of certain fundamental roles. The objective of this investigation, therefore, is to understand how religion is approached by Freud in the development of his work. As a means of addressing this issue, the method was guided by a theoretical investigation that (a) incorporated a specialized bibliography, (b) the author's published texts in his complete works, as well as, (c) the documentary material found in correspondence and biographies, bearing in mind the theme of religion under key words such as: metaphysics, religion, religiosity, worldview, God, gods, Judaism, Christianity, monotheism, totemism, illusion, helplessness, historical-truth, primeval father . The theoretical axis of this investigation articulated two registers of development of the theme of religion in the author's work: (1) his psychoanalytic anthropology, (2) and his metapsychological rereading of the phenomena. The results obtained from this dissertation indicate how Freud situates religion in an anthropology, essentially through three roles that this institution plays in culture: (1) the cosmological role of explaining the origin of the world and the totality of reality; (2) the ethical role of limiting the disruptive impulses of sociability, and the presentation of ideal models of behavior; (3) the role of emotional support in the face of the structural condition of human being's helplessness. Furthermore, the result of this investigation reflects how Freud understands that religion translates, from his worldview, a complex dimension linked to human desires, and proposes, on the other hand, to reread the phenomena described by religion through psychoanalytic theory, thus performing an epistemological turn that rearticulates metaphysics into a metapsychology